Time Budget Pressure and Work Stress Effects on Auditor Performance: Job Burnout as Mediator - Mutiara, Putu Kezya; Budiadnyani, Ni Putu; Mimaki, Caren Angellina (Journal of Trends Economics and Accounting Research, 2025)
This study investigates the influence of work stress and time budget pressure on auditor performance, with job burnout as a mediating variable. The study is grounded in Job Demands–Resources (JD-R) Theory and Maslach Burnout Theory, which explain how job demands affect employee well-being and performance. Using a quantitative approach, data were collected from 65 auditors working in public accounting firms in Bali through structured questionnaires and analyzed using SmartPLS. The results indicate that work stress and time budget pressure do not have a direct effect on auditor performance. However, both variables significantly increase job burnout. Job burnout has a significant negative effect on auditor performance and mediates the relationship between work stress and performance. In contrast, although time budget pressure contributes to higher burnout, its indirect effect on performance through burnout is not significant, suggesting that auditors may perceive time constraints as a routine job demand that can be managed without substantially reducing performance. These findings emphasize the critical role of burnout in translating work stress into performance outcomes and provide practical implications for public accounting firms in managing workloads, strengthening support systems, and promoting a healthy work environment to sustain audit quality.